2009
DOI: 10.1021/jp902814d
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Charge Transfer and Energy Level Alignment at Organic/TiO2 Interfaces

Abstract: Adsorption of titanyl phthalocyanine (TiOPc) on rutile TiO 2 (110) modified by a set of pyridine derivatives (2,2′-bipyridine, 4,4′-bipyridine, and 4-tert-butyl pyridine) has been investigated using synchrotron radiation based X-ray photoelectron spectroscopy (XPS). For the unmodified TiOPc/TiO 2 system, a strong charge transfer is observed from the first layer TiOPc into the substrate, which leads to a molecular layer at the interface with a depleted highest occupied molecular orbital (HOMO). However, precove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…The growth is of island type at room temperature. In agreement with previous studies on Pc/TiO 2 , [13][14][15][16] it is found that charge is transferred away from the molecular HOMO into the substrate. Further comparison between NEXAFS resonance shifts and PES shifts points to a considerable screening difference between molecular center and periphery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The growth is of island type at room temperature. In agreement with previous studies on Pc/TiO 2 , [13][14][15][16] it is found that charge is transferred away from the molecular HOMO into the substrate. Further comparison between NEXAFS resonance shifts and PES shifts points to a considerable screening difference between molecular center and periphery.…”
Section: Discussionsupporting
confidence: 92%
“…TiO 2 is usually used as the working electrode for such devices. Previously, we have found that Pc molecules (FePc, 13,14 TiOPc, 15 and H 2 Pc (Ref. 16)) suffer from electron depletion when absorbed on TiO 2 .…”
Section: Introductionmentioning
confidence: 97%
“…, the direction of the TiO 2 reconstruction rows) composed from slightly tilted phthalocyanines that are presumably partially overlapping was observed. Yu et al also investigated the adsorption of TiOPc on rutile (110) and on buffer layers formed by 2,2′-bipyridine, 4,4′-bipyridine, and 4-tert-butyl pyridine using X-ray absorption spectroscopy [57]. TiOPc molecules adsorbed directly on the rutile surface were observed to strongly bind with a significant charge transfer occurring into the substrate.…”
Section: Phthalocyaninesmentioning
confidence: 99%
“…Manipulation of the M Pc-substrate interaction is possible by either decorating the molecules (adding external atoms or molecules to the center or the periphery of Pcs) [43][44][45], by modifying the substrate by inserting intermediate layers [46,47], or by adding layers on top of M Pc [48][49][50][51][52]. For instance, upon adsorption of pyridine on an ordered layer of FePc on Au(111), pyridine molecules coordinate to the iron.…”
Section: Introductionmentioning
confidence: 99%